A Report of Two Cases of Mylopathy Due to Brucellosis - Ali Akbar Rezaei (پزشکی بالینی ابن سینا, 2001)
Brucellosis is relatively prevalent in undeveloped countries. Meningitis is one of the most common complications of neurobrucelloss but mylopathy is very rare. We report here two cases of brucellosis mylopathy that they referred to department of neurology in Hamadan Sina hospital in 1999 with weakness of lower extremity , difficulty in gait and urine incontinancy. Although various differential diagnosis were suspected for them but the diagnosis of brucellosis  mylopathy for both was established by accompanying signs and symptoms and paraclinic examination.